2021
DOI: 10.1080/14763141.2021.1952298
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the inter-lap stability and relationship between the race time and start, clean swim, turn and finish variables in elite male junior swimmers’ 200 m freestyle

Abstract: 2021): Assessment of the inter-lap stability and relationship between the race time and start, clean swim, turn and finish variables in elite male junior swimmers' 200 m freestyle, Sports Biomechanics,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Regarding these turn section times, variation was largest 5 m before wall contact [13,14] and similar to the variation in clean swimming performance [13]. However, there was a lower variation for the first 15 m after wall contact [13], probably due to the streamlined body position adopted during the underwater phase, making this section less fatigued. Although velocity is well maintained in one of the multiple turn sections, fatigue or changes in race strategy in another turn section of more than the 0.5%, as mentioned earlier, may result in a significant performance deterioration over the total race time [15].…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…Regarding these turn section times, variation was largest 5 m before wall contact [13,14] and similar to the variation in clean swimming performance [13]. However, there was a lower variation for the first 15 m after wall contact [13], probably due to the streamlined body position adopted during the underwater phase, making this section less fatigued. Although velocity is well maintained in one of the multiple turn sections, fatigue or changes in race strategy in another turn section of more than the 0.5%, as mentioned earlier, may result in a significant performance deterioration over the total race time [15].…”
Section: Introductionsupporting
confidence: 54%
“…In short-course races, the contribution of acyclic phases, i.e., start and turns, to the total race time is widely known [16,29,30]. For instance, turn times contributed 32.92 ± 1.09% to total race time in long-course 200 m races [13] compared to 50.84 ± 0.28% in 200 m shortcourse races [16]. Recent research studies investigated the effect of various turn sections on race time and suggested that faster IN-5m times would increase turn performance [25,31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations